2021
DOI: 10.3390/molecules26226791
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Protein-Protein Interactions within Acyl Carrier Protein (MmcB)-Dependent Modifications in the Biosynthesis of Mitomycin

Abstract: Mitomycin has a unique chemical structure and contains densely assembled functionalities with extraordinary antitumor activity. The previously proposed mitomycin C biosynthetic pathway has caused great attention to decipher the enzymatic mechanisms for assembling the pharmaceutically unprecedented chemical scaffold. Herein, we focused on the determination of acyl carrier protein (ACP)-dependent modification steps and identification of the protein–protein interactions between MmcB (ACP) with the partners in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…Inactivating mitB, mitC, mitD, or mitE exclusively led to a mutant strain that cannot produce mitomycin C (Figure S6). Different from a similar study by Kang et al, 21 we observed a trace of mitomycin C when mitF was inactivated (Figure S6). Thus, mitF is not indispensable for mitomycin biosynthesis in S. caespitosus, and its function could be partially substituted by certain NAD(P)H-dependent reductase gene(s) outside of the mit cluster.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Inactivating mitB, mitC, mitD, or mitE exclusively led to a mutant strain that cannot produce mitomycin C (Figure S6). Different from a similar study by Kang et al, 21 we observed a trace of mitomycin C when mitF was inactivated (Figure S6). Thus, mitF is not indispensable for mitomycin biosynthesis in S. caespitosus, and its function could be partially substituted by certain NAD(P)H-dependent reductase gene(s) outside of the mit cluster.…”
Section: Resultscontrasting
confidence: 99%
“…caespitosus ATCC 27422, a strain with a product profile in which mitomycin C is dominant, we validated the involvement of mmcB (the discrete ACP protein-encoding gene) in mitomycin biosynthesis (Figure ). Clearly, mmcB is necessary, as demonstrated independently by Dairi et al and Kang et al , We then engineered mmcB to a gene coding for C-terminally 8 × His-tagged MmcB-I (Figure S2) and examined whether this variant can substitute for the function of wild-type MmcB in S. caespitosus.…”
Section: Resultsmentioning
confidence: 90%